MAXIMUM REINFORCEMENT LENGTH OF AXIAL LOADED CFA PILES IN SOFT SOIL (Academic journal Industrial Machine Building Civil Engineering, 2017)
It is analyzed methods of different countries on the calculation of Continuous Flight Auger (CFA) on axial loads with considerable thickness of weak soils. It is proposed to improve the state standards of Ukraine for determine the maximum reinforcement length of axial loaded CFA piles in soft soil. Keywords: CFA pile, longitudinal bending, soft soil, reinforcement length.